Antiprejudicial Education in the Information Society - Cabanova, Vlasta (Communications - Scientific letters of the University of Zilina, 2007)
Prejudices are the main obstacles to successful implementation of multicultural principle in the life of the Slovak society. The prejudices create a consequential obstacle to good interpersonal relations for the sake of moral deficit manifested in condemning and consequent nonobjective judgement of different people as will as in social life phenomena.